PEMANFAATAN BUILDING INFORMATION MODELLING (BIM) PADA PERANCANGAN STRUKTUR BAJA TERHADAP BEBAN GEMPA - Pinta Astuti; Rangga Kurnianto; Surya Dewi Puspitasari (Jurnal Teknik Sipil, 2023)
This study focuses on designing the steel structure construction toward earthquake load, which uses Istana Qur’an as a research object. Modeling and designing the steel structural building by using two different software, SAP2000, and Tekla Structure. In the making process, the authors made presumptions on workload according to Indonesian Design Standards such as minimum design loads, seismic load design, seismic load for steel structure design, and joints in steel structure. Not only from a structural strength view for human safety but also the construction time and material cost are also able to be estimated which is becoming faster and more affordable compared to implementing the conventional method. As a full analysis result, in this steel design, there are six different steel profiles were used for steel building construction. For instance, IWF 440.300.11.18 as the column, IWF 350.175.7.11 and IWF 250.125.6.9 as the beams, IWF 200.100.5,5.8 as the gable roof frame, UNP 150.75.9.12,5 as purlin and L 150.150.15 as collar tie.